18p— syndrome with a single central maxillary incisor. Issue 5 (October 1981) - Dolan, Lawrence M; Willson, Kathryn; Wilson, William G
Abstract : A child with a single central maxillary incisor and a deletion of the short arm of chromosome 18 (18p—) is presented. He is the first patient in whom this association has been found.